Analysis Of Abnormal Stock Returns One Week After The First Confirmed Covid-19 Case in Indonesia - Made Arvin Ariantara; Ni Putu Riza Oktayanti; I Made Astawa; I Gede Made Bagus Wira Manuaba; Ni Wayan Ariestiani; Kadek Alexs Padma Widiadana (AIBPM Publisher, 2025)
This study examines the reaction of the Indonesian capital market to the announcement of the first confirmed COVID-19 case in Indonesia on March 2, 2020, by applying an event study approach to stocks included in the IDX SRI-KEHATI index. The sample consists of 25 companies, with an observation window of 11 trading days (t?5 to t+5) and an estimation period of 60 days. Abnormal returns were calculated using the market model to identify short-term market reactions to unexpected public information. The results indicate that the majority of stocks experienced negative abnormal returns around the event date, reflecting heightened investor uncertainty. On the announcement day (t?), several major stocks recorded significant negative abnormal returns, such as BBRI (?0.03361), BBNI (?0.03042), BTPS (?0.04307), and a negative accumulated abnormal return (ARTN) of ?0.02313. Although a limited number of stocks, including ASII (0.05942) and ANTM (0.03915), showed positive abnormal returns, the overall average abnormal return (AAR) declined sharply after the event. The cumulative average abnormal return (CAAR) continued to decrease throughout the post-event period, indicating a sustained negative market response. These findings support the semi-strong form of the Efficient Market Hypothesis, suggesting that the Indonesian capital market reacts quickly but unevenly to systemic crisis information